STS2 deficiency revives CD8+T cells from exhaustion and augments checkpoint blockade efficacy in cancer immunotherapy - Chunxiao Li; Fei Ma; Ying Zhang; Ting Wang; Hongnan Mo; Ning Zhong; Dongkui Xu; Fangzhou Sun; Yantong Zhou; Jianbin Guo; Zhenguo Zhao; Xiaoqi Yang; et al. (Journal for ImmunoTherapy of Cancer)
Background T-cell exhaustion is a major barrier to effective antitumor immunity and limits the efficacy of cancer immunotherapies. This study investigates the role of suppressor of T-cell signaling 2 (STS2, also known as UBASH3A) in regulating CD8+ T-cell exhaustion within the tumor microenvironment.Methods We used genetic ablation of STS2 in mouse models to assess tumor control and responses to anti-programmed cell death protein 1 (PD-1) checkpoint blockade therapy. CD8+ tumor-infiltrating lymphocytes (TILs) were characterized through flow cytometry, mass cytometry, and single-cell transcriptomics. Mechanistic studies included co-immunoprecipitation, protein degradation assays, and endocytosis measurements to elucidate the interplay between STS2 and PD-1.Results STS2 expression progressively increased with T-cell exhaustion. Genetic deletion of STS2 enhanced tumor control and improved responses to anti-PD-1 therapy. STS2-deficient CD8+ TILs maintained a more functional state, exhibiting enhanced effector activity, proliferation, and antitumor efficacy while resisting terminal exhaustion. Mechanistically, we discovered that STS2 physically interacts with PD-1 and modulates its expression, endocytosis, and degradation at the protein level.Conclusions Our findings establish STS2 as a multifaceted regulator of T-cell exhaustion and highlight its potential as a therapeutic target for enhancing antitumor immunity and improving cancer immunotherapy outcomes.